PERSEPSI KEMUDAHAN DAN KEGUNAAN ACONEX (STUDY DESKRIPTIF MENILAI PERSEPSI KEMUDAHAN DAN PERSEPSI KEGUNAAN ACONEX OLEH PENGGUNA DI PROYEK THAMRIN 9 PT. ACSET INDONUSA) - Yuni Siswantoro (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
PT. ACSET INDONUSA is one construction company under the auspices of the Astra Group. The company has many construction projects in several regions in Indonesia, one of which is a project Thamrin 9 Jakarta. The purpose of this study is to investigate and assess the Aconex system used by the company to assist in the documentation and project administration views from the perception of convenience and usability. The method used is the method of TAM (Technology Acceptance Model) with the help of AMOS software. Results obtained Factors that affect the acceptance of the project using Aconex system include the ability to self Thamrin on the computer, perceived ease of use, perceived usefulness, attitude to use, behavioral intention to use, and actual use of the system. So the Aconex system can improve the delivery and storage of documents (upload and send).